Volodymyr Fedorovych Homrach - "Orthopaedics, Traumatology; Prosthetics", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
February 27, 2020 marks the 60th anniversary of the birth of the traumatologist Khomrach Vladimir Fedorovich.